The New Era : American Thought and Culture in the 1920s. - Murphy, Paul (American thought and culture., 2011)
The New Era examines American thought and culture in the 1920s through the eyes of a generation of American intellectuals who became tribunes of openness, experimentation, and tolerance. The book tracks the emergence of a new set of arguments and.